1994
DOI: 10.1126/science.8171322
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Development of Peripheral Lymphoid Organs in Mice Deficient in Lymphotoxin

Abstract: Mice rendered deficient in lymphotoxin (LT) by gene targeting in embryonic stem cells have no morphologically detectable lymph nodes or Peyer's patches, although development of the thymus appears normal. Within the white pulp of the spleen, there is failure of normal segregation of B and T cells. Spleen and peripheral blood contain CD4+CD8- and CD4-CD8+ T cells in a normal ratio, and both T cells subsets have an apparently normal lytic function. Lymphocytes positive for immunoglobulin M are present in increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
722
3
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 931 publications
(741 citation statements)
references
References 34 publications
13
722
3
3
Order By: Relevance
“…LTa À/À , LTb À/À and LTbR À/À mice display severe developmental defects in lymph node and Peyer's patch neogenesis, a disorganized lymphoid microarchitecture and lack of mature follicular dendritic cells (Pfeffer et al, 1993;De Togni et al, 1994;Koni et al, 1997;Futterer et al, 1998;Ngo et al, 1999). In addition, LTa À/À and LTbR À/À mice show inflammatory disorders in nonlymphoid organs (for example, lung, liver, kidney; (Fu et al, 1997(Fu et al, , 2000Fu and Chaplin, 1999;Chin et al, 2003).…”
Section: Ltbr Activation and Nf-jb Signalingmentioning
confidence: 99%
“…LTa À/À , LTb À/À and LTbR À/À mice display severe developmental defects in lymph node and Peyer's patch neogenesis, a disorganized lymphoid microarchitecture and lack of mature follicular dendritic cells (Pfeffer et al, 1993;De Togni et al, 1994;Koni et al, 1997;Futterer et al, 1998;Ngo et al, 1999). In addition, LTa À/À and LTbR À/À mice show inflammatory disorders in nonlymphoid organs (for example, lung, liver, kidney; (Fu et al, 1997(Fu et al, , 2000Fu and Chaplin, 1999;Chin et al, 2003).…”
Section: Ltbr Activation and Nf-jb Signalingmentioning
confidence: 99%
“…The LTA cytokine is produced by lymphocytes and mediates a large number of inflammatory, immunostimulatory and antiviral responses [6]. The role of LTA was demonstrated as essential for the normal development of peripheral lymphoid organs in mice models [14]. It was shown that administration of LTA in NOD mice and Bio-Breeding (BB) rats may have modulated autoimmunity and prevented development of T1DM [15].…”
Section: Introductionmentioning
confidence: 99%
“…8 Studies of natural functions of LT by production of an LT-deficient mouse strain suggest an essential role for LT in the normal development of peripheral lymphoid organs. 9 Mice deficient in LT have no morphologically detectable lymph nodes or Peyer's patches, although the thymus appears to be normal. Within the white pulp of the spleen, there is a failure of normal segregation of B and T cells, and lymphocytes positive for immunoglobulin M are present in increased numbers in both the spleen and peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
“…Within the white pulp of the spleen, there is a failure of normal segregation of B and T cells, and lymphocytes positive for immunoglobulin M are present in increased numbers in both the spleen and peripheral blood. 9 Moreover, LT has been found to be an autocrine growth factor for EBV-infected B cell lines. 10 In this report we analyzed the potential role of LT in CLL, a low-grade B cell malignancy.…”
Section: Introductionmentioning
confidence: 99%